Aplikasi Pelayanan Pariwisata dan Ekonomi Kreatif Salatiga Berbasis Web Menggunakan Framework Laravel - Anthonio Stefanus; Suprihadi Suprihadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Online The ministry of tourism and the creative economy was part of organizing government affairs in tourism and the creative economy to assist the President in organizing state governments. Salatiga’s cultural and tourist services should definitely bring knowledge and information to the community so that the people in salatiga can better understand the quality and professional standards available in salatiga. The municipality of salatiga had not yet had a medium to publish information about tourism and the creative economy to the public, so a medium was needed to propagate that information. The purpose of this study is to design applications for the creative economic service information system and web-based tourism using the framework laravel. The design of the application isa website of the creative economic service information system and tourism that can make it easier for salatiga urban communities to access the information available to salatiga.